The COPE / DOAJ / OASPA / WAME Principles of Transparency and Best Practice in Scholarly Publishing: A Critical Analysis - Teixeira da Silva, Jaime A.; Moussa, Salim (ETHICS IN PROGRESS, 2024)
Four publishing-related organizations, the Committee on Publication Ethics (COPE), the Directory of Open Access Journals (DOAJ), the Open Access Scholarly Publishers Association (OASPA), and the World Association of Medical Editors (WAME), the first being dedicated specifically to the creation and dissemination of ethics policies, established a set of 16 principles related to journal and publisher transparency and “best” publishing practices. The first, second, third and fourth versions were published in 2013, 2015, 2018, and 2022, respectively. Membership of these organizations implies that members can only become such if they satisfy these principles. This paper compares the four versions to appreciate how the content has changed over time, as a historical endeavor to gather how publishing ethics has progressed over time. An assessment is also made to determine whether all principles are related to transparency and best principles, and if any may be missing. We concluded that the 16 principles offer broad guidance to several important aspects related to journal and publishing ethics and management. However, the vast majority are in general excessively broad, occasionally vague, or lack sufficient examples or specifics, despite the slight improvement between versions 3 and 4. We argue further that these weaknesses may limit their practical application. Until September 2022, there was no transparency regarding the consequences for any members that might violate, or not abide by, these principles. In the light of these arguments, we are of the opinion that the 16 principles of “best” publishing practices merit additional improvements.